2003
DOI: 10.1001/archpedi.157.7.665
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of Adolescents in Hawaii With Obsessive-compulsive Disorder

Abstract: The characteristics of OCD in this sample suggest the need to consider the possibility of a streptococcal origin and the need for further studies to clarify the genetic and environmental risk factors for OCD in Hawaiian and other Polynesian youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…In the Italian study by , 17-year-olds with OCD did not differ from agematched subjects without obsessive-compulsive symptoms and other adolescents in terms of job status (student, employed, and unemployed). In a Hawaiian sample, Guerrero et al (2003) did not find a significant relationship between the presence of OCD in adolescents and the main wage earner's employment status, a finding that was also reported in Poland by Brynska and Wolanczyk (2005). In sum, no specific relationship between employment and OCD were found in younger samples.…”
Section: Gendermentioning
confidence: 54%
See 3 more Smart Citations
“…In the Italian study by , 17-year-olds with OCD did not differ from agematched subjects without obsessive-compulsive symptoms and other adolescents in terms of job status (student, employed, and unemployed). In a Hawaiian sample, Guerrero et al (2003) did not find a significant relationship between the presence of OCD in adolescents and the main wage earner's employment status, a finding that was also reported in Poland by Brynska and Wolanczyk (2005). In sum, no specific relationship between employment and OCD were found in younger samples.…”
Section: Gendermentioning
confidence: 54%
“…For examples, although Karno et al (1988) reported that the ECA prevalence of OCD among college graduates was higher than that among those with some college education, the pattern was reversed for high school education, such that the prevalence of OCD among people who had graduated from high school was lower than that of subjects who had completed some high school. Similarly, Guerrero et al (2003) found that the lower the main wage earners' education, the higher the rate of OCD among children and adolescents in Hawaii. Finally, Crino et al (2005) were unable to find educational differences between people with and without OCD in an Australian sample.…”
Section: Educationmentioning
confidence: 90%
See 2 more Smart Citations
“…The failure to detect shared environmental influences is likely due to a lack of statistical power associated with insufficient sample size. Although the results of studies were not consistent, several investigators found that low family socioeconomic status (SES) was a risk factor for the development of OCD and that children with OCD came from larger families than did normal controls (e.g., Guerrero et al, 2003;Heyman et al, 2001). Given the previous finding that streptococcal infection can trigger OCD (Kiessling et al, 1993), the causal shared environmental factor for OCD might be streptococcal infection common in low SES families rather than low SES itself.…”
Section: Discussionmentioning
confidence: 99%